(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2025)
Amid the still-dominant critical approaches to religion in the public sphere— particularly those targeting Christianity—more balanced voices have emerged, pointing to the need for a renewed reflection on Christianity’s place in Western culture. While it is too early to speak of a clear trend or a lasting shift in discourse, recent public commentaries, such as Marcin Matczak and Tomasz Stawiszyński’s writings, suggest a growing interest in Christianity’s cultural significance. Although these interventions do not adopt an apologetic tone, they may be interpreted as attempts to articulate a moderate position that avoids ideological extremes and transcends conventional political divisions. It appears that within the mainstream Polish media, a narrative is beginning to take shape—one that is sympathetic to the defence of so-called cultural Christianity.